Predictability and strategic behavior under frontier regulation. (February 2020) - Agrell, Per J.; Teusch, Jonas
Abstract: Frontier-based yardsticks, as applied in European energy network regulation, are not immune to strategic behavior. Under yardstick regulation, the regulator gauges the operator against a cost target set by the other firms in the sector. Many regulators have implemented frontier-based yardsticks where the cost function is defined by the most efficient firms (peers). This paper demonstrates that when it is possible to predict peers in advance, firms can manipulate the frontier to their advantage. We single out horizontal mergers as a plausible means to achieve such strategic objectives and develop a measure to identify strategic mergers ex ante. Using data from the electricity distribution sector in Norway that is subject to stable frontier-based regulation allows us to identify firm behavior that is consistent with our predictions. The paper contributes to the modern yardstick literature as existing evidence of strategic behavior in related regulatory settings is either based on anonymized questionnaire responses from regulatory authorities or relies on simulations using unidentified firms that are not actually exposed to such benchmarking in practice. The paper concludes by discussing policy implications. Highlights: Yardstick regulation promotes efficiency in electricity networks. Real applications assume that firm cannot distort the frontier. Frontier and peer impact from mergers can be measured. The metrics identify potentially strategic mergers. In Norway, the metric indicates strategic mergers.